Plasma‐Derived C1 Esterase Inhibitor for Acute Antibody‐Mediated Rejection Following Kidney Transplantation: Results of a Randomized Double‐Blind Placebo‐Controlled Pilot Study. Issue 12 (27th June 2016) - Montgomery, R. A.; Orandi, B. J.; Racusen, L.; Jackson, A. M.; Garonzik‐Wang, J. M.; Shah, T.; Woodle, E. S.; Sommerer, C.; Fitts, D.; Rockich, K.; Zhang, P.; Uknis, M. E.
Abstract : Antibody‐mediated rejection (AMR) is typically treated with plasmapheresis (PP) and intravenous immunoglobulin (standard of care; SOC); however, there is an unmet need for more effective therapy. We report a phase 2b, multicenter double‐blind randomized placebo‐controlled pilot study to evaluate the use of human plasma‐derived C1 esterase inhibitor (C1 INH) as add‐on therapy to SOC for AMR. Eighteen patients received 20 000 units of C1 INH or placebo (C1 INH n = 9, placebo n = 9) in divided doses every other day for 2 weeks. No discontinuations, graft losses, deaths, or study drug‐related serious adverse events occurred. While the study's primary end point, a difference between groups in day 20 pathology or graft survival, was not achieved, the C1 INH group demonstrated a trend toward sustained improvement in renal function. Six‐month biopsies performed in 14 subjects (C1 INH = 7, placebo = 7) showed no transplant glomerulopathy (TG) (PTC+cg≥1b) in the C1 INH group, whereas 3 of 7 placebo subjects had TG. Endogenous C1 INH measured before and after PP demonstrated decreased functional C1 INH serum concentration by 43.3% (p < 0.05) for both cohorts (C1 INH and placebo) associated with PP, although exogenous C1 INH–treated patients achieved supraphysiological levels throughout. This new finding suggests that C1 INH replacement may be useful in the treatment of AMR. Abstract : This phase 2b randomized, placebo‐controlled pilot study evaluates the use of human plasma–derived C1 esterase inhibitor (C1 INH) as add‐on therapy to standard of care for antibody‐mediated rejection, and while the primary end point was not achieved, there were no safety signals.